Mineral Composition of Lentils: Physiological Functions, Antinutritional Effects, and Bioavailability Enhancement - Asmaa Benayad; Youssef Aboussaleh (Journal of Food Quality)
Lentil (Lens culinaris) is an important nutritious crop, grown and consumed throughout the world due to its high macro- and micronutrients contents, including minerals. Minerals have several beneficial influences on human health. Thus, lentils play a major role in food security, particularly among low-income countries. The current review aims to highlight the present knowledge on the mineral composition of lentils, compare it with the recommended dietary allowance and adequate intake of minerals, investigate the literature regarding its physiological role, give detailed information on different antinutritional factors preventing its bioavailability, and present adopted solutions to enhance the bioavailability of minerals in lentil seeds. Thereby, a literature search was conducted using reliable sources: Elsevier, Springer, PubMed, and CrossRef. Based on the previous studies, 100 g of cooked lentils, for example, may be enough to cover the recommended dietary allowance/adequate intake of iron in infants under six months and children aged one to three years. One hundred grams of cooked lentils may also cover the recommended dietary allowance/adequate intake of zinc and magnesium in infants and children aged one to three years. Hence, it is imperative that the scientists continue to show the significance of pulses as a mineral source and their effects on human health. Indeed, lentils should be exploited for a variety of purposes, mainly towards eliminating malnutrition, on the condition of being well-balanced. Lentils should be incorporated either in snacks or while preparing household, school, or hospital meals, particularly in developing countries.